DIARY of a Wimpy Kid : THE GET AWAY - Kinney, Jeff (United States Amulet Books, 2017)
Diary of a Wimpy Kid: The Getaway (Book 12) follows Greg Heffley and his family escaping a stressful Christmas for a tropical island resort, Isla de Corales. The trip quickly devolves into a chaotic nightmare filled with sunburns, venomous creatures, food poisoning, and lost luggage, turning their supposed paradise into a disaster.
English
Keywords: Children's Novel; Graphic Novel